2017
DOI: 10.3389/fnbot.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Motor Primitive-Based Control for Leg Exoskeletons during Continuous Multi-Locomotion Tasks

Abstract: An emerging approach to design locomotion assistive devices deals with reproducing desirable biological principles of human locomotion. In this paper, we present a bio-inspired controller for locomotion assistive devices based on the concept of motor primitives. The weighted combination of artificial primitives results in a set of virtual muscle stimulations. These stimulations then activate a virtual musculoskeletal model producing reference assistive torque profiles for different locomotion tasks (i.e., walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 44 publications
0
26
0
1
Order By: Relevance
“…As proposed in many papers [ 7 , 23 ], transparency is a key feature that a robotic device should have to provide valuable assistance to patients in rehabilitation. While remarkable efforts have been done in the literature to design devices and controllers for achieving transparency [ 23 , 24 , 42 ], few works have investigated the potential of a modular description of the neuromuscular system in evaluating the properties of a device. In this paper, it is suggested that muscle synergies may be considered for comparing motor modules underlying movement in free movements and robot-assisted ones, providing a user-centered view of the transparency properties of the device.…”
Section: Discussionmentioning
confidence: 99%
“…As proposed in many papers [ 7 , 23 ], transparency is a key feature that a robotic device should have to provide valuable assistance to patients in rehabilitation. While remarkable efforts have been done in the literature to design devices and controllers for achieving transparency [ 23 , 24 , 42 ], few works have investigated the potential of a modular description of the neuromuscular system in evaluating the properties of a device. In this paper, it is suggested that muscle synergies may be considered for comparing motor modules underlying movement in free movements and robot-assisted ones, providing a user-centered view of the transparency properties of the device.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitive amplification control (SAC) method is a kind of zero torque control method that is widely used for load-carrying exoskeleton robots. Kazerooni and Huang et al [144]- [146] are renowned for their design of the human augmentation exoskeleton robot BLEEX. To simplify the control, they gave the BLEEX three distinct states that manifest three different dynamic models: single support; double support; and double support with redundancy.…”
Section: Interaction Force-based Torque Assistmentioning
confidence: 99%
“…A PI-based motor current regulator is used to provide low-level control. Garate et al [144,145] have presented a gait phase estimation-based control structure that is intended to help pilots in complicated terrain. The gait phase is estimated by an AFO whilst, at the same time, the walking intention is estimated to determine the terrain.…”
Section: Gait Feature Estimation-based Torque Assistancementioning
confidence: 99%
“…The third experimental activity was carried out in seven healthy subjects [46]. The orthotic devices were controlled based on a novel motor primitives approach based on an adaptive-oscillator phase detector.…”
Section: B Usability Studiesmentioning
confidence: 99%